Perceptions and practices of technology usage in English language curriculum implementation among instructors and students in Somaliland higher education institutions - Khadar, Mustafe; Melesse, Tadesse; Siyoum, Yilfashewa; Basha, Garkebo (Bahir Dar Journal of Education, 2024)
This study aimed to investigate how instructors and students in Somaliland’s higher education institutions perceive and utilize technology in implementing the English language curriculum. The study involved 93 English language instructors and 377 students from both public and private universities. The instructors and students were selected using available sampling and proportionate stratified random sampling techniques respectively. Data was collected through a survey questionnaire and analyzed quantitatively using mean, standard deviation, one-sample test, independent samples t-test, and linear regression. The findings indicated that both instructors and students had low perceptions of the benefits of technology in English language teaching, and instructors had limited experience in implementing technology-supported curriculum. However, the study revealed a strong relationship between technology usage and successful curriculum implementation. Therefore, it was recommended that instructors and students receive training on educational technology awareness and practical application to enhance the English language curriculum implementation.